I servizi pubblici per le adozioni tra norma giuridica e nuove complessità familiari. Un contributo alla riflessione interdisciplinare - Chiodini, Silvia (Antropologia Pubblica, 2018)
Italian law still define adoption as “closed”, cutting off any tie with biological family. Nevertheless, adoptees are more and more keepers of structured memories. In any case, they are actors of complex trajectories of life and tangled stories. In a wider context, it seems clear that adoption reality overcomes the narrow boundaries of law as well as the analytic prospective of professionalism and established practices. Therefore, today's adoptive complexity requires a redefinition of the dominant device: as a professional of an Adoption Centre, my contribution highlights the need of a change in approaching the issue by training to face adoption through new tools which allow us to better integrate the past, the present and the future of adoptees and their family connections. Field experiences lead to deal with different situations and often there is a sense of great confusion. In this situation, the professional's orientation influences the adoptee's possibility to access or not access to information related to his/her story. A guided knowledge of this information would allow he/she to be able to give a meaning to his/her own experience and create a fully meaning connection between the biological belonging and the adoptive one, that is an essential aspect to structuring an adoption really responding to the interest of the adopted child. From this view, the question is not to search for and to know one’s own origin relatives, but how to direct oneself to give sense to the living experience of adoption by referring to multiple roots and belonging.